Regulation and control method for phosphogypsum crystal transformation
By mixing it with sulfuric acid and adding specific additives in the phosphogypsum transformation process, the reaction conditions are controlled to achieve simultaneous control of dihydrate gypsum to α-semi-water gypsum and anhydrous gypsum, the problem of increasing the difficulty of complex solvent systems and whiteness in the existing process is solved, and efficient phosphogypsum transformation and whiteness improvement is achieved.
Patent Information
- Application Number
- CN202411568579.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-18
AI Technical Summary
The existing phosphogypsum transformation process has the problem of complex solvent system and difficulty in controlling α-hemihydrogypsum and anhydrous gypsum at the same time, and it is difficult to improve the whiteness.
By mixing phosphogypsum with 15-40 wt% sulfuric acid evenly and performing stirring reaction, the concentration of sulfuric acid and the stirring reaction time are controlled, and polymerized sulfate and ethylenediaminetetraacetic acid disodium salt are added to the mixture as additives to achieve simultaneous control of dihydrate gypsum to α-hemihydrate gypsum and anhydrous gypsum, and the whiteness is increased.
The simultaneous control of dihydrate gypsum to α-semi-water gypsum and anhydrous gypsum is achieved, which improves the whiteness of the product without high temperature burning, saves costs, and realizes the high-value utilization of phosphogypsum.
Smart Images

Figure CN119638232A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of phosphogypsum processing, and in particular to a method for regulating phosphogypsum crystal transformation. Background Art
[0002] Phosphogypsum is divided into dihydrate gypsum (CaSO4·2H2O) and hemihydrate gypsum (CaSO4·1 / 2H2O), with the majority being gypsum containing two waters. At present, the world's total annual output of wet-process phosphoric acid is about 270 million tons (in terms of P2O5), with about 150 million tons of by-product phosphogypsum, and an utilization rate of only 4.3% to 4.6%. Natural stacking of phosphogypsum has become the main treatment method, which not only consumes a lot of money and occupies a lot of land, but also causes continuous pollution of the atmosphere, groundwater system and soil due to wind erosion and rain erosion if stacked for a long time.
[0003] Therefore, in order to realize the green sustainable circular development of phosphate fertilizer chemical industry, how to effectively process phosphogypsum to avoid pollution has become a problem to be solved. At present, the effective way of comprehensive utilization of phosphogypsum is to produce cement with sulfuric acid from phosphogypsum, but this method needs to invest huge funds and has high energy consumption, large pollution, unstable product quality, and technically there are also some bottlenecks that hinder its promotion. The application of phosphogypsum in the fields of building materials, soil conditioner and road construction also has the problems of secondary pollution and low product added value, so it is necessary to develop high value-added products to realize the sustainable development of wet phosphoric acid industry and reduce environmental pollution.
[0004] Phosphogypsum crystallization technology is a technology that converts industrial byproduct phosphogypsum into high value-added products. Although it has both environmental and economic benefits, there are still some shortcomings in the existing technology. For example, the current phosphogypsum crystallization process has problems such as complex solvent systems, and it is also difficult to achieve simultaneous control of α-hemihydrate gypsum and anhydrous gypsum and improve whiteness. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a method for regulating the crystal transformation of phosphogypsum. The method provided by the present invention realizes the simultaneous control of the transformation of dihydrate gypsum into α-hemihydrate gypsum and anhydrous gypsum, and simultaneously achieves the improvement of whiteness.
[0006] In order to solve the above technical problems, the present application provides a method for regulating the crystallization of phosphogypsum. The technical solution provided in the present application is described below:
[0007] The first aspect of the present application provides a method for regulating phosphogypsum crystal transformation, comprising:
[0008] The phosphogypsum and sulfuric acid are uniformly mixed and stirred for reaction; the concentration of the sulfuric acid is 15-40wt%.
[0009] Optionally, the usage ratio of the phosphogypsum to sulfuric acid is 25g:100mL.
[0010] Optionally, the stirring reaction temperature is 100° C., and the stirring reaction time is 0.25-5 h.
[0011] Optionally, the process further comprises adding an additive after uniformly mixing the phosphogypsum and sulfuric acid.
[0012] Optionally, the additive is used in an amount of 4 wt % of the phosphogypsum.
[0013] Optionally, the additives are polysulfate and disodium ethylenediaminetetraacetic acid.
[0014] Optionally, the mass ratio of the polysulfate to disodium ethylenediaminetetraacetic acid is 1:1.
[0015] Optionally, the polysulfate is polyaluminum sulfate; the disodium salt of ethylenediaminetetraacetic acid is calcium disodium ethylenediaminetetraacetate or magnesium disodium ethylenediaminetetraacetate.
[0016] It can be seen from the above technical solutions that this application has the following advantages:
[0017] The invention realizes the simultaneous control of converting dihydrate gypsum into alpha-hemihydrate gypsum and anhydrous gypsum by controlling the concentration of sulfuric acid and the time of stirring reaction.
[0018] The invention adds an additive to a mixture of sulfuric acid and phosphogypsum, thereby achieving an effect of increasing whiteness while crystallizing the phosphogypsum.
[0019] The method provided by the invention does not require high-temperature burning, saves costs, and realizes high-value utilization of phosphogypsum. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution in the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 a is the XRD graph of the phosphogypsum in Example 1 in a 15wt% sulfuric acid solution at different crystal transformation times, and b is the XRD graph of the crystal transformation for 4h;
[0022] Figure 2 The XRD diagram of phosphogypsum in Example 2 at different crystal transformation times in a 20wt% sulfuric acid solution;
[0023] Figure 3The XRD diagram of phosphogypsum in Example 3 at different crystal transformation times in a 40wt% sulfuric acid solution;
[0024] Figure 4 This is the XRD diagram of phosphogypsum in comparative example 1 at different crystal transformation times in a sulfuric acid-free solution. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0026] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0030] The invention provides a method for regulating and controlling phosphogypsum crystal transformation, comprising mixing phosphogypsum and sulfuric acid uniformly and then stirring the mixture for reaction; the concentration of the sulfuric acid is 15-40wt%.
[0031] As the acid concentration increases, dihydrate gypsum is transformed into α-hemihydrate gypsum. When the sulfuric acid concentration is greater than 20wt%, dihydrate gypsum is directly transformed into anhydrous gypsum without the appearance of hemihydrate gypsum phase.
[0032] In some embodiments, the usage ratio of the phosphogypsum to sulfuric acid is 25 g:100 mL.
[0033] In some embodiments, the stirring reaction temperature is 100° C., and the stirring reaction time is 0.25-5 h.
[0034] In some embodiments, the stirring reaction time is 0.25 h, 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.
[0035] In the present invention, as the stirring reaction time increases, the phosphogypsum is gradually dissolved, and the impurity ions gradually diffuse into the solution, thereby improving the whiteness. However, if the reaction time is too long, the whiteness will decrease. This is because if the reaction time is too long, the dissolved impurity ions will be back-adsorbed during the recrystallization process, resulting in a decrease in whiteness. Therefore, the present invention controls the reaction time to be within 5 hours. If it exceeds 5 hours, the whiteness will decrease.
[0036] In some embodiments, the step of uniformly mixing the phosphogypsum and the sulfuric acid further includes adding an additive.
[0037] In some embodiments, the additive is used in an amount of 4 wt % of the phosphogypsum.
[0038] The present invention has found that the addition of additives can increase the whiteness of phosphogypsum. When the amount of additives is 4wt%, the crystal transformation time of phosphogypsum will be shortened. Under the same time, the increase in the amount of additives will shorten the time for whiteness enhancement.
[0039] In some embodiments, the additives are polysulfate and disodium ethylenediaminetetraacetic acid.
[0040] In some embodiments, the mass ratio of the polysulfate to disodium ethylenediaminetetraacetic acid is 1:1.
[0041] In some embodiments, the polysulfate is polyaluminum sulfate; the disodium salt of EDTA is calcium disodium EDTA or magnesium disodium EDTA.
[0042] In some embodiments, the method for regulating the crystallization of phosphogypsum specifically comprises the following steps:
[0043] Add phosphogypsum to the sulfuric acid solution, stir evenly, add polyaluminum sulfate and calcium disodium ethylenediaminetetraacetate, and stir to react after the above chemicals are dissolved.
[0044] After the reaction is completed, the mixture is cooled to room temperature, filtered and washed until neutral, and dried in an air dryer. The whiteness of the dried sample is measured using a whiteness meter, and the crystal structure of the obtained crystallized product is characterized using an X-ray scanning diffractometer.
[0045] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0046] The phosphogypsum used in the embodiments comes from a chemical plant in Guizhou, and the phosphogypsum is aged phosphogypsum or fresh phosphogypsum.
[0047] Embodiment 1:
[0048] 20 g of old phosphogypsum is added to 150 mL of a 15 wt % sulfuric acid solution, stirred evenly, polyaluminum sulfate and calcium disodium ethylenediaminetetraacetate (the amount of polyaluminum sulfate is 2 wt % of the old phosphogypsum, and the amount of calcium disodium ethylenediaminetetraacetate is 2 wt % of the old phosphogypsum), stirred and reacted at 100 ° C for different times, filtered and washed to neutrality, and then dried, the whiteness of the dried sample was measured using a whiteness meter, and an X-ray diffractometer was used to determine the crystal form change process.
[0049] Embodiment 2:
[0050] Add 20 g of fresh phosphogypsum to 150 mL of 20 wt% sulfuric acid solution, stir evenly, add polyaluminum sulfate and calcium disodium ethylenediaminetetraacetate (the amount of polyaluminum sulfate is 2 wt% of the fresh phosphogypsum, and the amount of calcium disodium ethylenediaminetetraacetate is 2 wt% of the fresh phosphogypsum), stir and react at 100 ° C for different times, filter and wash until neutral, and then dry, use a whiteness meter to measure the whiteness of the dried sample, and use an X-ray diffractometer to determine the crystal change process.
[0051] Embodiment three:
[0052] Add 20 g of fresh phosphogypsum to 150 mL of 40 wt% sulfuric acid solution, stir evenly, add polyaluminum sulfate and calcium disodium ethylenediaminetetraacetate (the amount of polyaluminum sulfate is 2 wt% of the fresh phosphogypsum, and the amount of calcium disodium ethylenediaminetetraacetate is 2 wt% of the fresh phosphogypsum), stir and react at 100 ° C for different times, filter and wash until neutral, and then dry, use a whiteness meter to measure the whiteness of the dried sample, and use an X-ray diffractometer to determine the crystal change process.
[0053] Comparative Example 1:
[0054] Add 20 g of fresh phosphogypsum to 150 mL of deionized water, stir evenly, add polyaluminum sulfate and calcium disodium ethylenediaminetetraacetate (the amount of polyaluminum sulfate is 2 wt% of the fresh phosphogypsum, and the amount of calcium disodium ethylenediaminetetraacetate is 2 wt% of the fresh phosphogypsum), stir and react at 100 ° C for different times, filter and wash until neutral, and then dry, use a whiteness meter to measure the whiteness of the dried sample, and use an X-ray diffractometer to determine the crystal change process.
[0055] The changes in whiteness and particle size under different implementation conditions in Examples 1-3 and Comparative Example 1 are shown in Table 1.
[0056] The gypsum yield after crystallization of phosphogypsum under different implementation conditions in Examples 1-3 is shown in Table 2.
[0057] Table 1 Changes in whiteness and particle size under different implementation conditions
[0058]
[0059] It can be seen from Table 1 that with the increase of acid concentration, the whiteness of phosphogypsum gradually increases, indicating that the increase of acid concentration causes the original gypsum to dissolve and recrystallize, and the impurity ions are dissolved, resulting in an increase in whiteness; at the same concentration, with the extension of reaction time, the whiteness also tends to increase gradually, indicating that with the increase of reaction time, phosphogypsum is gradually dissolved, and the impurity ions gradually diffuse into the solution, thereby improving the whiteness; and without adding acid, only adding additives, the whiteness also increases with the increase of reaction time, indicating that the additives can interact with the impurity ions in the phosphogypsum. According to the salt effect, as time goes on, more impurity ions are precipitated, thereby improving the whiteness.
[0060] Table 2 Gypsum yield after crystallization under different implementation conditions in Examples 1-3 (%)
[0061]
[0062] The phosphogypsum in Examples 1-3 and Comparative Example 1 was characterized by XRD. Figure 1 is the XRD diagram of Example 1, Figure 1 As can be seen from Figure a, at a lower acid concentration, as the reaction time is extended to 4 h, Figure 1 In b, the coexistence of dihydrate gypsum, α-hemihydrate gypsum and anhydrous gypsum was observed. Figure 2 (XRD pattern of Example 2) and Figure 3 It can be seen from the XRD diagram of Example 3 that the increase in acid concentration is more conducive to the transformation of the crystal form. After only 15 minutes of reaction, the phosphogypsum is directly transformed from dihydrate gypsum to anhydrous gypsum. As the reaction time increases, the crystal form remains anhydrous gypsum. Figure 4 (XRD diagram of comparative example 1) It can be seen that at a concentration without adding acid, only adding additives, the crystal form of phosphogypsum does not change and is still dihydrate gypsum. As the reaction time increases, the crystal form does not change.
[0063] From Table 1, Table 2 and Figure 1-3It can be seen that with the increase of acid concentration, the dihydrate gypsum is more completely transformed into anhydrous gypsum, and the impurities in the dihydrate gypsum are dissolved, which improves the whiteness. When the acid concentration increases to 40%, the yield of the final crystallization product is the lowest, but all of it is anhydrous gypsum. When the acid concentration is 15%, dihydrate gypsum still exists. As the reaction time increases to 4h, the dihydrate gypsum gradually transforms into a mixed phase of semi-hydrate and anhydrous gypsum, resulting in a decrease in the yield of the final crystallization product.
[0064] Therefore, from the above results, it can be seen that when the acid concentration is between 15% and 20%, dihydrate gypsum can be transformed into α-hemihydrate gypsum. When the acid concentration is higher than 20%, dihydrate gypsum is directly transformed into anhydrous gypsum without the appearance of hemihydrate gypsum phase. At the same time, with the increase of acid concentration, whiteness gradually increases; at the same acid concentration, with the increase of reaction time, whiteness increases.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for regulating the crystallization of phosphogypsum, characterized in that: include: The phosphogypsum and sulfuric acid are uniformly mixed and stirred for reaction; the concentration of the sulfuric acid is 15-40wt%.
2. The method for controlling the crystallization of phosphogypsum according to claim 1, characterized in that: The dosage ratio of the phosphogypsum to sulfuric acid is 25g:100mL.
3. The method for controlling the crystallization of phosphogypsum according to claim 1, characterized in that: The stirring reaction temperature is 100° C., and the stirring reaction time is 0.25-5 h.
4. The method for controlling the crystallization of phosphogypsum according to claim 3, characterized in that: The stirring reaction time is 0.25h, 0.5h, 1h, 2h, 3h, 4h or 5h.
5. The method for controlling the crystallization of phosphogypsum according to claim 1, characterized in that: The method further comprises adding additives after uniformly mixing the phosphogypsum and sulfuric acid.
6. The method for controlling the crystallization of phosphogypsum according to claim 5, characterized in that: The amount of the additive is 4 wt % of the phosphogypsum.
7. The method for controlling the crystallization of phosphogypsum according to claim 5 or 6, characterized in that: The additives are polysulfate and disodium ethylenediaminetetraacetic acid.
8. The method for controlling the crystallization of phosphogypsum according to claim 7, characterized in that: The mass ratio of the polysulfate to disodium ethylenediaminetetraacetic acid is 1:
1.
9. The method for controlling the crystallization of phosphogypsum according to claim 7, characterized in that: The polysulfate is polyaluminum sulfate; the disodium salt of ethylenediaminetetraacetic acid is calcium disodium ethylenediaminetetraacetate or magnesium disodium ethylenediaminetetraacetate.